Mobile phone screen protector glass: A TL investigation of the intrinsic background signal - Céline Bassinet; Michael Discher; Yoann Ristic; Clemens Woda (Frontiers Media S.A., 2022)
Screen protector glasses are often used to protect the display screen surface of mobile phones against physical damage. Their dosimetric properties were recently studied by thermoluminescence with the aim of using these items as potential emergency dosimeters in the event of a radiological accident. They are sensitive to ionizing radiation and they could be easily removed and replaced without destroying the phone in case of a dose assessment. However, an intrinsic background signal that partially overlaps with the radiation-induced TL signal is observed. The reconstructed dose could be overestimated if not properly taken into account. The homogeneity of this confounding signal on the surface of several screen protectors was estimated and a chemical treatment with hydrofluoric acid (HF 40%) was tested to minimize its contribution. For most of the samples studied, the intrinsic background signal remained a serious issue for dose reconstruction. Additionally, the TL signals were measured in the red detector range using two different models of red-sensitive photomultiplier tubes. The homogeneity of the intrinsic background signal on the surface of screen protectors was examined and the results of the reduction of this signal by the chemical HF treatment were discussed.